THE DISCOURSE OF PEACE, UNITY AND COMMON FEELINGS IN THE CYPRIOT TURKISH POETRY OF THE NEW MILLENNIUM - Erol SAKALLI (Fırat University, 2019)
The Cypriot Turkish literature went through a process in which the dominant theme was “independence” as a result of political and cultural pressures and separatist and alienating policies just before the Peace Operation. That this process was evolved into “freedom” after the 1974 Peace Operation, led to the themes of “unity and peace” to be dominant in the literature. In addition to the writers and poets who experienced both periods, the contemporary ones who learned the periods though their parents’ stories have been the spokesmen of the painful struggle in the literature. A number of themes, from lyrism to didactic elements, are covered in the Cypriot Turkish literature on a wide range of topics which carry the epic traces of an old history. This variety in the literature also results from that the Cypriot Turks are not a closed society but have the feelings that all Turkic peoples have. They reflect the pride and conscious of being a part of the Turkic World into their poems. In this study, we will investigate the perspective of the Cypriot Turks of peace, unity, and the common feelings of the Turkic World through the poems from contemporary Cypriot Turkish literature.